Rational medication use review: a quality assurance/improvement process for HIV/AIDS treatment programmes - Fomundam, Henry; Maranga, Andrew; Tesfay, Abraham; Chanetsa, Lucia; Muzola, Vieira; Thierry, Nkurabagaya; Kambafwile, Henry (International Journal of Research in Medical Sciences, 2017)
Background: A Rational Medication Use Review (RMUR) was conducted at four facilities providing antiretroviral therapy in Burundi as a simple and practical strategy for service providers and programme managers to continuously assess and monitor quality of ART services provided. Methods: A comprehensive data collection tool was developed to systematically and retrospectively capture relevant data from randomly selected ART patient files in the four ART facilities. Results: ART data from 157 patients receiving ART services from four facilities was extracted and analysed. WHO stage 4 AIDS defining diseases were recorded in 125 (79.6%) of the patients at the time of ART initiation. The most frequent opportunistic infections and/or co-morbidities were cryptosporidiosis (14.4%), HIV wasting (14.4%), tuberculosis (13%) and candidiasis (17.4%). 97.8% of the patients were taking concomitant medicines. A large percentage of patients (72.4%) had done a baseline CD4 test before initiation of therapy with a majority of the patients (85.8%) getting their lab results within one week of the collection of the specimens. For some patients (9%), it took up to 8 weeks to get test results. About 21.8% of the patients were hospitalized at least once while on ART and 11.2% of the hospitalized patients died. Conclusion: " RMUR is a simple and practical strategy that can be appropriately modified to suite local settings. It offers a cost-effective and participatory method of identifying and correcting factors that may negatively impact the quality of care and desired outcomes for patients on ART.